(untitled) (Marketing Journal, 2025)
The article examines the current state and development issues of fruit and vegetable production in the agrarian sector of our republic and its regions. Key measures for enhancing agriculture in the context of modern technological advancements are proposed. The necessity of strengthening the role of the state in developing territorial aspects of agrarian policy and implementing renewed agrarian reforms to ensure food security is emphasized.